TCNQ-BASED POROUS COORDINATION POLYMERS SYNTHESIS AND SORPTION PROPERTIES STUDY IN MAGNETIC FIELD - Zubir, Moondra; Hamasaki, Atom; Ozeki, Sumio (Sainstek : Jurnal Sains dan Teknologi, 2015)
Porous coordination polymers (PCPs) were synthesized with used TCNQ anion that acts as cross linker connecting and bipyridine to form a 3D framework.  In these study, we use zinc and manganese metal ion as centre of complex coordination.  Green crystal of Zn(TCNQ-TCNQ)bpy.1.5 benzene and Mn(TCNQ-TCNQ)bpy.1.5 benzene was successfully synthesized  in no under magnetic field (0T) and under magnetic field 6T.  XRD patterns of Zn(TCNQ-TCNQ)bpy.1.5 benzene 0T and 6T shown not significant different pattern that indicate no different crytal formed.  XRD patterns of Mn(TCNQ-TCNQ)bpy.1.5 benzene also shown not significant different but we found five different intensity ratio peaks that possibility it was a little bit changing of crystal structure.   To investigate the pores properties, adsorption isotherm was performe for oxygen gas in 77 K and the guest of benzene were removed at 413 K for 3 hours under low pressure.  Zn(TCNQ-TCNQ)bpy}1.5benzene 0T and 6T oxygen adsorption isotherms  shows the unique sorption isotherms by gate pressure profile.  On other hand, Mn(TCNQ-TCNQ)bpy}1.5 benzene 0T and 6T shows type 1 adsorption isotherms for micropores materials.  Adsorption isotherm was also determined in magnetic field 6T for all crystal, and shows shift of gate pressure for Zn compounds and enhance the amount of oxygen adsorbed for all kind of compounds.Key words: porous coordination polymers, polymers synthesis, magnetic field